EVALUATION OF PARENTERAL ANTICOAGULANTS USE IN COVID-19 PATIENTS AT A HOSPITAL IN SIAK DISTRICT - Anggraeni, Silvana
COVID-19 can trigger a cytokine storm and systemic hyper inflammation leading to increased activation of coagulation and resulting in hypercoagulability. The hypercoagulable state in COVID-19 patients increases the risk of thrombosis and thromboembolism. Parenteral anticoagulants are used for thromboprophylaxis and treatment of thrombosis in COVID-19 patients. Anticoagulants are associated with a high percentage of drug-related problems. The study aimed to evaluate the use of parenteral anticoagulants in patients with confirmed COVID19 and determine the variables that influence drug-related problems. The study was conducted retrospectively by taking samples of medical record data from patients hospitalized in the Pinere ward from March-October 2021. Analysis of parenteral anticoagulant drug-related problems (DRP) using PCNE 9.1. The results showed that fondaparinux (53.66%) was the most commonly administered parenteral anticoagulant. Of 123 subjects, there were 63 subjects experienced drugrelated problems and 60 subject did not experience the drug-related problem. Drug interactions (51.61% of cases) and too frequent regimens (23.66%) were the most common potential causes of drug-related problems. There were 6 cases of bleeding and 7 cases of suspected heparin-induced thrombocytopenia. Chi-square was used to analyze the relationship between potential drugrelated problems and influencing factors. The type of care (intensive care unit and not admitted to intensive care unit) showed a statistically significant relationship with the incidence of DRP (p<0.05). Based on bivariate and multivariate analysis, the type of care showed a significant relationship to the incidence of DRP (p<0.05). The odds ratio (OR) value is 4,630 with a confidence interval of 1.224-17.513. From this study, some COVID-19 patients who used anticoagulant experienced drug-related problems. moreover, patients admitted to the intensive care unit are at risk of experiencing DRP of 4.630 times compared to patients not admitted to ICU.